Analisis Penanganan Masalah Banjir dengan Sumur Resapan - Cut Suciatina Silvia; Meylis Safriani (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2020)
Kuta Padang village is located in the city of Meulaboh, where the problems that often is flood and inundation caused by the capacity of drainage channels that are not able to accommodate runoff discharge and due to changes in land use into trade areas. The purpose of this study are apply the infiltration wells technique as an effort and strategic for handling inundation and flood by excessive rainwater runoff in drainage channels and as an alternative to groundwater conservation in minimize surface runoff. The results of Permeability test show that the value of the permeability coefficient (k) = 6,283.10-5 m/sec or 22.62 cm/hour with a types of soil in Kuta Padang Village including fine sand soils with a low permeability classification and satisfy the technical requirements of SNI No. 03-2453-2002 in infiltration well planning. At the location of research study, can be implemented planning individual infiltration wells and communal infiltration wells. Individual infiltration wells with a diameter of 1 meter or radius = 0.5 meter and depth of 2 meters. Communal infiltration well with discharge based on the area of the house and yard and planning discharge based on the area of the roof is planned to be 2 meters in diameter well or radius = 1 meter and depth of 2.5 meters. total required of communal infiltration wells is 30 units and 33 units with flood discharge efficiencies > 95%.